Self-consistent calculation of tunneling current in w-GaN/AlGaN(0001) two-barrier heterostructures; Semiconductors; Vol. 40, iss. 6 - Grinyaev S. N. Sergey Nikolaevich (Low-Dimensional Systems, 2006)
Title screen